2013
DOI: 10.1007/s13762-013-0460-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of manganese nodules leaching residue for adsorption of nickel(II) ions from aqueous solution

Abstract: Deep ocean manganese nodules are significant futuristic resource of copper, nickel and cobalt. After recovery of these valuable metals, a huge quantity of residue (*70 % of ore body) is generated. In the present paper, investigations carried out for the application of washed manganese nodule leaching residue (wMNR) for the removal of nickel (Ni) ions from aqueous solution by adsorption are described. Several parameters have been varied to study the feasibility of using wMNR as potential adsorbent for remediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The residues generated by NH 3 -SO 2 leaching of manganese nodules were successfully used as an adsorbent of Ni 2+ , Cr 6+ , Cu 2+ , Cd 2+ and Pb 2+ [4,5,[16][17][18], with removal efficiency strongly dependent on pH, temperature and usually initial metal ion concentration in the solution. Randhawa et al found that manganese nodule residue obtained from reduction roasting followed by ammoniacal leaching is an acceptable adsorbent of Ni 2+ with good regenerability [19]. The leach residues were also used as an effective selenite adsorbent with the best adsorption capacity at pH 5 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The residues generated by NH 3 -SO 2 leaching of manganese nodules were successfully used as an adsorbent of Ni 2+ , Cr 6+ , Cu 2+ , Cd 2+ and Pb 2+ [4,5,[16][17][18], with removal efficiency strongly dependent on pH, temperature and usually initial metal ion concentration in the solution. Randhawa et al found that manganese nodule residue obtained from reduction roasting followed by ammoniacal leaching is an acceptable adsorbent of Ni 2+ with good regenerability [19]. The leach residues were also used as an effective selenite adsorbent with the best adsorption capacity at pH 5 [20,21].…”
Section: Introductionmentioning
confidence: 99%